Application of Geographic Information System (GIS) in Soil Erosion Prediction: A Case Study of the Sg. Weng Experimental Watersheds - Tan, Albert Thean Wei (2002)
A study was carried out to assess soil erosion under natural forest in watershed using the Universal Soil Loss Equation (USLE) model within a Geographic Information System (GIS) environment. The Sg. Weng Experimental Watershed, located within Hulu Muda Forest Reserve, Kedah, Malaysia was chosen for this study. The study area comprised four watersheds namely Watershed 1 (2.6 sq. Ion), Watershed 2 (8.4 sq. Ion), Watershed 3 (7.6 sq. Ion) and Watershed 5 (42.1 sq. Ian). The USLE model consists of five factors namely rainfall erosivity (R), soil erodibility (K), length slope (LS), crop management (C) and support practice (P) factors. The R factor was obtained based on four methods namely Morgan (1974), Balamurugan (1990), Roose (1977) and rainfall equal or exceeding 25 mmIhr (this study). Using a regular grid of Digital Elevation Model (OEM), a method based on the maximum downhill slope and cumulative slope length was used for calculating the LS factor. K factor was obtained from Department of Agriculture, Kedah based on five soil series. The C and P were combined into a single factor called vegetation management (VM). The values obtained for each parameter were later converted to raster layers for modeling the soil erosion.